Comparative efficacy and safety of SGLT2is and ns-MRAs in patients with diabetic kidney disease: a systematic review and network meta-analysis - Yang, Si-Qi; Zhao, Xi; Zhang, Jing; Liu, Huan; Wang, Yu-Han; Wang, Yao-Guang (Frontiers in Endocrinology, 2024)
Objectives To evaluate the efficacy and safety of non-steroid mineralocorticoid receptor antagonists (ns-MRAs) and sodium-glucose cotransporter 2 inhibitors (SGLT2is) in patients with diabetic kidney disease (DKD). Methods Systematic literature searches were performed using PubMed, Embase and Web of Science encompassing inception until January 20, 2024. Randomized control trials (RCTs) comparing ns-MRAs and SGLT2is in DKD were selected. The efficacy outcomes of interest included kidney-specific composite outcome, cardiovascular (CV)-specific composite outcome, end-stage kidney disease (ESKD), and overall mortality. We also investigated safety outcomes, including acute kidney injury (AKI) and hyperkalemia. Results A total of 10 randomized clinical trials with 35,786 patients applying various treatments were included. SGLT2is (SUCRA 99.84%) have potential superiority in kidney protection. SGLT2is (RR 1.41, 95%CI 1.26 to 1.57) and ns-MRAs (RR 1.17, 95% CI 1.08 to 1.27) were associated with significantly lower kidney-specific composite outcome than the placebo. Regarding the reduction in CV-specific composite outcome and ESKD, SGLT2is (SUCRA 91.61%; 91.38%) have potential superiority in playing cardiorenal protection. Concerning the CV-specific composite outcome (RR 1.27, 95%CI 1.09 to 1.43) and ESKD (RR 1.43, 95%CI 1.20 to 1.72), SGLT2is significantly reduced the risks compared to placebo. Regarding the reduction in overall mortality, SGLT2is (SUCRA 83.03%) have potential superiority in postponing mortality. Concerning the overall mortality, SGLT2is have comparable effects (RR 1.27, 95%CI 1.09 to 1.43) with placebo to reduce the risk of overall mortality compared to placebo. For AKI reduction, ns-MRAs (SUCRA 63.58%) have potential superiority. SGLT2is have comparable effects (RR 1.24, 95%CI 1.05 to 1.46) with placebo to reduce the risk of AKI. For hyperkalemia reduction, SGLT2is (SUCRA 93.12%) have potential superiority. SGLT2is have comparable effects (RR 1.24, 95%CI 1.05 to 1.46) with placebo to reduce the risk of AKI. Concerning hyperkalemia reduction, nsMRAs (RR 1.24 95%CI 0.39 to 3.72) and SGLT2is (RR 1.01 95%CI 0.40 to 3.02) did not show significant benefit compared to placebo. Conclusion Concerning the efficacy and safety outcomes, SGLT2is may be recommended as a treatment regimen for maximizing kidney and cardiovascular protection, with a minimal risk of hyperkalemia in DKD. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier CRD42023458613.